Local Wisdom-Based Character Education for Facing Globalization Strategic Issues in The Digital Era in Primary School Student - Layli, Fithriyyatul; Shidiq, Galih Albarra; Qomariah, Nurul (DAS Institute, 2023)
In the era of globalization and increasingly advanced information technology, education faces challenges in maintaining students' moral quality and local culture. Globalization has negative impacts, such as addiction to online shows and games and losing traditional local wisdom values. The digital generation phenomenon also affects students' character with declining manners, moral decadence, and weak socio-cultural value education. Therefore, education needs to reconstruct educational learning processes by the basic principles of proper education. Teachers are essential in developing education through the cultural and technological advances that form in society. In addition, as parents, it is crucial to introduce good technology to students by understanding their needs, installing applications that support creativity, and limiting excessive consumption. Character education based on local wisdom is strategic in building student character. Teachers can choose curriculum components developed in learning modules. Character education based on local knowledge can help prevent students’ characters from falling into the adverse effects of globalization.